Nanostructured lipid carriers based mRNA vaccine leads to a T cell–inflamed tumour microenvironment favourable for improving PD-1/PD-L1 blocking therapy and long-term immunity in a cold tumour modelResearch in context - Carole Fournier; Marion Mercey-Ressejac; Valentin Derangère; Amal Al Kadi; David Rageot; Christine Charrat; Alexis Leroy; Julien Vollaire; Véronique Josserand; Marie Escudé; Séverine Escaich; François Ghiringhelli; et al. (EBioMedicine)
Summary: Background: mRNA-based cancer vaccines show promise in triggering antitumour immune responses. To combine them with existing immunotherapies, the intratumoral immune microenvironment needs to be deeply characterised. Here, we test nanostructured lipid carriers (NLCs), the so-called Lipidots®, for delivering unmodified mRNA encoding Ovalbumin (OVA) antigen to elicit specific antitumour responses. Methods: We evaluated whether NLC OVA mRNA complexes activate dendritic cells (DCs) in vitro and identified the involved signalling pathways using specific inhibitors. We tested the anti-tumoral impact of Ova mRNA vaccine in B16-OVA and E.G7-OVA cold tumour-bearing C57Bl6 female mice as well as its synergy effect with an anti-PD-1 therapy by following the tumour growth and performing immunophenotyping of innate and adaptive immune cells. The intratumoral vaccine-related gene signature was assessed by RNA-sequencing. The immune memory response was assessed by re-challenging surviving treated mice with tumour cells. Findings: Our vaccine activates DCs in vitro through the TLR4/8 and ROS signalling pathways and induces specific T cell activation while exhibits significant preventive and therapeutic antitumour efficacy in vivo. A profound intratumoral remodelling of the innate and adaptive immunity in association with an increase in the gene expression of chemokines (Cxcl10, Cxcl11, Cxcl9) involved in CD8+ T cell attraction were observed in immunised mice. The combination of vaccine and anti-PD-1 therapy improves the rates of complete responses and memory immune responses compared to monotherapies. Interpretation: Lipidots® are effective platform for the development of vaccines against cancer based on mRNA delivery. Their combination with immune checkpoint blockers could counter tumour resistance and promote long-term antitumour immunity. Funding: This work was supported by Inserm Transfert, la Région Auvergne Rhône Alpes, FINOVI, and the French Ministry of Higher Education, research and innovation (LipiVAC, COROL project, funding reference N° 2102992411).